The Factors Influencing Semarang University (USM) Students' Preferences In Using Online Transportation - Marshush, Ummi Hanifah; Murni, Murni; Hilmansyah, Hilmi (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2024)
Semarang city, as a metropolitan city, has not escaped the development of online transportation. There are several online transportation that are often used, namely Gojek, Grab and Maxim. The existence of online transportation can provide additional choices of transportation modes that can be used. Choosing online transportation to carry out daily activities cannot be separated from the push and pull factors for each individual which are definitely different. Therefore, this research aims to determine the factors that influence Semarang University students' preferences for using online transportation. This research was conducted using quantitative methods and multiple linear regression analysis techniques. Overall internal factors influence USM students' preferences in using online transportation, namely (0.720) or 72%. However, the main factors that influence this are feelings of stress, difficulty getting parking and not having a private vehicle. Meanwhile, external factors as a whole influence USM students' preferences for using online transportation, namely (0.680) or 68%. The main factors that influence this are punctuality and ease of using online transportation.